Molecular interplays in hepatic stellate cells: apoptosis, senescence, and phenotype reversion as cellular connections that modulate liver fibrosis - Silva, Brenda de Oliveira da [UNESP]; Ramos, Leticia Ferrreira [UNESP]; Moraes, Karen C. M. [UNESP] (Wiley-Blackwell, 2017)
Liver fibrosis is a pathophysiological process correlated with intense repair and cicatrization mechanisms in injured liver, and over the past few years, the characterization of the fine-tuning of molecular interconnections that support the development of liver fibrosis has been investigated. In this cellular process, the hepatic stellate cells (HSCs) support the organ fibrogenesis. The HSCs are found in two distinct morpho-physiological states: quiescent and activated. In normal liver, most HSCs are found in quiescent state, presenting a considerable amount of lipid droplets in the cytoplasm, while in injured liver, the activated phenotype of HSCs is a myofibroblast, that secrete extracellular matrix elements and contribute to the establishment of the fibrotic process. Studies on the molecular mechanisms by which HSCs try to restore their quiescent state have been performed; however, no effective treatment to reverse fibrosis has been so far prescribed. Therefore, the elucidation of the cellular and molecular mechanisms of apoptosis, senescence, and the cell reversion phenotype process from activate to quiescent state will certainly contribute to the development of effective therapies to treat hepatic fibrosis. In this context, this review aimed to address central elements of apoptosis, senescence, and reversal of HSC phenotype in the control of hepatic fibrogenesis, as a guide to future development of therapeutic strategies.
Keywords: apoptosis; cellular senescence; hepatic fibrogenesis; hepatic stellate cells; phenotypic reversion